Molecularly Imprinted Carriers for Diagnostics and Therapy-A Critical Appraisal - Emilia Balcer; Monika Sobiech; Piotr Luliński (MDPI AG, 2023)
Simultaneous diagnostics and targeted therapy provide a theranostic approach, an instrument of personalized medicine-one of the most-promising trends in current medicine. Except for the appropriate drug used during the treatment, a strong focus is put on the development of effective drug carriers. Among the various materials applied in the production of drug carriers, molecularly imprinted polymers (MIPs) are one of the candidates with great potential for use in theranostics. MIP properties such as chemical and thermal stability, together with capability to integrate with other materials are important in the case of diagnostics and therapy. Moreover, the MIP specificity, which is important for targeted drug delivery and bioimaging of particular cells, is a result of the preparation process, conducted in the presence of the template molecule, which often is the same as the target compound. This review focused on the application of MIPs in theranostics. As a an introduction, the current trends in theranostics are described prior to the characterization of the concept of molecular imprinting technology. Next, a detailed discussion of the construction strategies of MIPs for diagnostics and therapy according to targeting and theranostic approaches is provided. Finally, frontiers and future prospects are presented, stating the direction for further development of this class of materials.